Species-specific effects of iron on temperate and tropical marine rotifers in reproduction, lipid and ROS metabolisms. (August 2021) - Han, Chengyan; Kim, Hee-Jin; Lee, Jae-Seong; Sakakura, Yoshitaka; Hagiwara, Atsushi
Abstract: Two euryhaline rotifers, the temperate species Brachionus plicatilis and tropical species Brachionus rotundiformis, were used to investigate the effects of iron (FeSO4 ·7H2 O), an essential trace metal, on reproductive patterns and lifetables, including the metabolism of lipid and reactive oxygen species (ROS). B. plicatilis was more sensitive to iron with regard to sexual reproduction. While iron had no significant effect on the population growth at 0–48 μg/mL, it caused a decrease in the resting egg production. B. plicatilis exposed to 6 and 12 μg/mL of iron showed an increase in the intracellular ROS levels and a decrease in the neutral lipid content in sexual organs, accompanied by downregulation of antioxidant components CuZnSOD and two cytochromes ( CYP clan 2&3). These patterns suggested that iron-induced oxidative stress was not neutralized by its antioxidant defense system, thus negatively affecting the fecundity of fertilized mictic females. However, B. rotundiformis showed a dose-dependent increase in population growth with extended lifespan and positive sexual reproduction in response to 0–24 μg/mL iron. Furthermore, compared to Fe-exposed B. plicatilis, B. rotundiformis showed better antioxidant mechanism, whereas genes involved in lipid synthesis (citrate lyase, mitochondrial CYP ) and reproduction ( vasa, sirtuin-2 ) were significantly upregulated compared to the control, implying that B. rotundiformis was likely to have higher resilience in response to iron-induced oxidative stress. These findings suggest that iron is likely to cause interspecific interactions in the B. plicatilis species complex, whereas the tropical species B. rotundiformis may have evolved an effective defense mechanism against iron-induced stress. Graphical abstract: Image 1 Highlights: Iron effects varied in the temperate and tropical species of euryhaline rotifers. Iron negatively affected the sexual reproduction of temperate species. Iron stimulated antioxidant response and lipid synthesis in tropical species. Iron should affect rotifer reproductive patterns with ROS and lipid metabolism.